The Effect of Emotional Intelligence on the Assertive Behavior of Students in Grade VII of SMP Negeri 5 Kupang in the 2024/2025 Academic Year - Maria Trisna More; Matilda Pia Bone; Maria Erlinda (Universitas Muhammadiyah Enrekang, 2025)
The aim of this research is to determine the effect of emotional intelligence on the assertive behavior of class VII students at SMP Negeri 5 Kupang for the 2024/2025 academic year. This research is a type of quantitative research. The variables in the research are the independent variable (X) emotional intelligence and the dependent variable (Y) assertive behavior. The population and sample in this study were 32 students in class VII C of SMP Negeri 5 Kupang for the 2024/2025 academic year. The data collection tool used was a questionnaire. Data analysis used simple linear regression analysis techniques and was processed using the SPSS for Windows version 26 application. The results of research data analysis showed that the t_count value .> ttable (41.107 > 0.361) at a significant level of 5% with df=n-2 (32-2 = 30). Apart from that, the significance value is 0.000 < 0.05, so the null hypothesis (H_0) is rejected, while the alternative hypothesis (H_a) is accepted, meaning that there is an influence of emotional intelligence on the assertive behavior of Class VII C students at SMP 5 Kupang for the 2024/2025 academic year.